Machine and Deep Learning Using MATLAB : Algorithms and Tools for Scientists and Engineers - Al-Malah, Kamal I. M. (John Wiley & Sons, Inc., 2024)
Machine and Deep Learning Using MATLAB introduces early career professionals to the power of MATLAB to explore machine and deep learning applications by explaining the relevant MATLAB tool or app and how it is used for a given method or a collection of methods. Its properties, in terms of input and output arguments, are explained, the limitations or applicability is indicated via an accompanied text or a table, and a complete running example is shown with all needed MATLAB command prompt code.